1998
DOI: 10.1002/(sici)1520-6297(199801/02)14:1<73::aid-agr7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of generic milk advertising impacts on markets in New York State

Abstract: This article examines the responsiveness of fluid milk sales to generic milk advertising in New York City, Albany, Syracuse, Rochester, and Buffalo markets. Fluid milk demand equations for New York City, Albany, Syracuse, Rochester, and Buffalo are estimated with monthly data for the period from January 1986 through June 1995. The results indicate that generic milk advertising is positive and statistically significant at the 10% significance level in each market. The highest advertising elasticity is in the Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…However, after some time period the effectiveness of this advertising effort starts to decline and reaches zero at time (L + 1). As in previous generic dairy product research, we model this behavior as a polynomial distributed lag (PDL), with end-point restrictions equal to zero (e.g., Lenz, Kaiser and Chung 1998;Kaiser 2000). In general notation, the total advertising effect on demand at time t using a PDL parametric structure with end-point restrictions can be written as: (14) where: β i = λ 0 + λ 1 i + λ 2 i 2 and β -1 = β L + 1 = 0 TADV t = the total advertising effect at time t accounting for the distributed lag effects ADV t-i = advertising expenditure at time t-i L = the total lag length λ 0 , λ 1 , λ 2 = PDL parameters to estimate.…”
Section: Description Of the Panel Of Us Householdsmentioning
confidence: 99%
“…However, after some time period the effectiveness of this advertising effort starts to decline and reaches zero at time (L + 1). As in previous generic dairy product research, we model this behavior as a polynomial distributed lag (PDL), with end-point restrictions equal to zero (e.g., Lenz, Kaiser and Chung 1998;Kaiser 2000). In general notation, the total advertising effect on demand at time t using a PDL parametric structure with end-point restrictions can be written as: (14) where: β i = λ 0 + λ 1 i + λ 2 i 2 and β -1 = β L + 1 = 0 TADV t = the total advertising effect at time t accounting for the distributed lag effects ADV t-i = advertising expenditure at time t-i L = the total lag length λ 0 , λ 1 , λ 2 = PDL parameters to estimate.…”
Section: Description Of the Panel Of Us Householdsmentioning
confidence: 99%
“…Several studies have also examined the use of healthcare advertising exposure measured by advertisement expenditures or gross rating points (GRPs), which are essentially a measure of people who have seen an advertisement and its processing or communication effects 32. Others have examined downstream effects of exposure to advertising on target audience action, such as product requests or sales data 33 34. However, much of the discussion in public health around advertising effectiveness and GRPs has taken place in the tobacco control arena.…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser (1997) found that retail, wholesale, and farm markets of dairy products in US were all influenced by the generic advertising. Lenz, Kaiser, and Chung (1998) estimated the responsiveness of fluid milk sales to advertising in the markets of New York City, Albany, Syracuse, Rochester, and Buffalo. They concluded that spending on generic milk advertising had been profitable for dairy farmers.…”
Section: Related Researchmentioning
confidence: 99%